2020
DOI: 10.1002/ar.24392
|View full text |Cite
|
Sign up to set email alerts
|

The History of the Synapse

Abstract: Why did I choose this particular topic for my lecture rather than the history of neuroscience or the history of the neuron? Simply because I believe that every disciple has the obligation to pay homage to their mentors once in their lifetime. My formation as a neuroscientist involved three such mentors spanned across three countries. The first was Spain, where I was born, completed my medical studies, and had my first glimpse of neuroscience at the Cajal Institute with Fernando de Castro. It was him who, in 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 150 publications
0
12
0
Order By: Relevance
“…Electrochemical transmission is the canonical mode of information processing by the nervous system (148,149). The evidence in this review demonstrates the feasibility of combining targeted and untargeted metabolomics to identify candidate molecules that modulate visceral functions of the prefrontal cortex.…”
Section: Conclusion Tensions and Future Directionsmentioning
confidence: 90%
“…Electrochemical transmission is the canonical mode of information processing by the nervous system (148,149). The evidence in this review demonstrates the feasibility of combining targeted and untargeted metabolomics to identify candidate molecules that modulate visceral functions of the prefrontal cortex.…”
Section: Conclusion Tensions and Future Directionsmentioning
confidence: 90%
“…Microscopy confirmed his first observations, and Leeuwenhoek (1695) showed that the nerves coming out of the brain were assembled in hollow fibrils [ 95 ]. However, it was only two centuries later that Cajal provided the basis for modern neuroscience, and Sherington would bring us into modern neurobiology, naming “synapse” what Cajal had previously identified as “nerve joint” [ 96 ].…”
Section: The Psychic Life Of Microorganismsmentioning
confidence: 99%
“…This allowed understanding the general principles of their organisations, from the simplest to the most complex ones. Importantly, Cajal hypothesised the existence of a relationship between the architecture of neural networks and their functionalities, a working basis that will remain until today at the heart of the reflection in attempts to elucidate the functioning of nervous systems [ 96 ]. In addition, Cajal’s artistic sense, the quality of his representations and his wonder brought conceptual and technical rigour to science but also blurred the boundaries between science and the arts [ 102 ].…”
Section: The Psychic Life Of Microorganismsmentioning
confidence: 99%
“…When sir Sherrington introduced the term 'synapsis' [1], it was still unknown whether or not nerve impulses reach their target through direct electrical coupling [2,3]. Together with other evidence, it was the visualization by electron microscopy of the synaptic cleft, the narrow gap between an axon and its target, which put the debate to rest in favor of transmitter-mediated neurotransmission [4][5][6].…”
Section: Introductionmentioning
confidence: 99%